Management of Islamic Character Strengthening thru School Culture at SMA Negeri 4 Tualang - Devi Fatwanti; Diana Diana; Yosie Kristin Pandriyani; Nisa’el Amala; Adit Yuliani; Muhammad Kholid Ramadhanzi; Syaiful Dinata (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
Strengthening Islamic character is one of the main objectives of education that needs to be systematically implemented thru school culture. The challenges of technological development, social change, and the moral degradation of students demand educational institutions to create a learning environment that can continuously internalize Islamic values. This study aims to analyze the management of strengthening Islamic character thru school culture at SMA Negeri 4 Tualang. The research uses a qualitative approach with a field research type. Data were obtained thru observation, interviews, and documentation involving the principal, the vise principal in charge of student affairs, and Islamic Religious Education teachers as informants. Data analysis was conducted thru stages of data reduction, data presentation, and conclusion drawing with triangulation techniques to ensure data validity. The research results show that the strengthening of Islamic character is carried out thru the organization of structured programs, clear task distribution, and coordination among all school members. The implementation of school culture is realized thru religious habituation, teacher role modeling, the integration of Islamic values in the learning process, as well as co-curricular and extracurricular activities that support the character formation of students. The success of the program is influenced by the commitment of school leaders, the exemplary behavior of teachers, the consistency of school culture, and collaboration between the school, family, and community, while the influence of social environments, the development of digital technology, and the heterogeneity of family backgrounds pose challenges in its implementation. This research concludes that a school culture managed systematically, consistently, and collaboratively is an effective strategy in strengthening students' Islamic character and supporting the creation of a religious and character-building educational environment.